1997
DOI: 10.1007/bf02475718
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of organic exhausts and the thermal stability of catalysts

Abstract: The catalytic combustion of various organic compounds has been investigated over noble and non-noble metal catalysts using a fixed bed. It was concluded that the activity order of different organic compounds on a noble metal catalyst is toluene > 2-butanone > benzene > n-heptane = isopropyl alcohol > acrylonitrile > cyclohexane. On non-noble metal catalyst, it is isopropyl alcohol > 2obutanone > acrylonitrile > toluene> n-neptune > cyclohexane > benzene. In order to compare the thermal stability of catalysts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Much research has focused on NO reduction by hydrogen and hydrocarbons as reducing agent, and the research on NO reduction by CO mainly focus on catalytic reduction. The use of CO as a reducing agent has advantages for NO x reduction in practical application, because of its presence in significant amounts in the combustion process. The CO oxidation is carried out by NO reduction, and NO removal is usually accomplished via reduction to form N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Much research has focused on NO reduction by hydrogen and hydrocarbons as reducing agent, and the research on NO reduction by CO mainly focus on catalytic reduction. The use of CO as a reducing agent has advantages for NO x reduction in practical application, because of its presence in significant amounts in the combustion process. The CO oxidation is carried out by NO reduction, and NO removal is usually accomplished via reduction to form N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thermal combustion at temperatures higher than 850 1C results in the emission of secondary pollutants (nitrogen oxides, NO x ), 7 while selective catalytic combustion (SCC), which is characterized by an operating temperature of 300-500 K, has a lower environmental impact. [8][9][10][11][12] Moreover, the inclusion of the oxidation process of acrylonitrile in models that simulate the combustion of coal and other low-rank fossil fuels is important to account for dangerous emissions. This is because the nitrogen content of many fuels is essentially ascribed to the presence of pyrrolic and pyridinic structures, [13][14][15] but their thermal decomposition generates many nitrogen-bearing compounds, including acrylonitrile, [16][17][18][19] that can undergo subsequent oxidation to NO x .…”
Section: Introductionmentioning
confidence: 99%
“…The most common catalysts used in VOCs abatement are noble metals (Pt, Pd and Rh) and transition metal oxides (Mn 2 O 3 , NiO, Cr 2 O 3 , V 2 O 5 ), dispersed on supports with high surface areas, such as alumina, silica and titania (Noordally et al, 1993;Zwinkels et al, 1993;Gandía et al, 2002;Álvarez-Galván et al, 2004). This study adopted a mixed ceramic honeycomb Pt/Pd catalyst to treat toluene, an important aromatic compound found in gasoline, and found a conversion rate of 95% at 230°C with an inflow toluene concentration of 2000 ppm, and a space flow speed of 40000/hr (Li et al, 1997), the Pt/γ-Al 2 O 3 catalysts prepared by sol-gel method showed higher thermal stability of metal particles than the conventional impregnation catalyst, because the exposed Pt metal particles strongly anchored onto the alumina support by metal-support oxygen bonding (Cho et al, 1998). It has been reported that Pt/HAUF causes methyl-isobutyl-ketone (MIBK) conversion to increase with oxygen concentration at low MIBK concentrations, and to increase at higher concentrations (Tsou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%